Designing Interfaces that Support Temporal Work Across Meetings with Generative AI - Vanukuru, Rishi; Panda, Payod; Chen, Xinyue; Scott, Ava Elizabeth; Tankelevitch, Lev; Rintel, Sean (DIS2025, 2025)
Temporal work is an essential part of the modern knowledge workplace, where multiple threads of meetings and projects are connected across time by the acts of looking back (retrospection) and ahead (prospection). As we develop Generative AI interfaces to support knowledge work, this lens of temporality can help ground design in real workplace needs. Building upon research in routine dynamics and cognitive science, and an exploratory analysis of real recurring meetings, we develop a framework and a tool for the synergistic exploration of temporal work and the capabilities of Generative AI. We then use these to design a series of interface concepts and prototypes to better support work that spans multiple scales of time. Through this approach, we demonstrate how the design of new Generative AI tools can be guided by our understanding of how work really happens across meetings and projects. KEYWORDS: videoconferencing, meetings, goal, recurring, temporal work, retrospection, prospection, intentionality, generative AI, support, tools RELATED RESEARCH Formative studies Mental Models of Meeting Goals: Supporting Intentionality in Meeting Technology Prototype studies Before meetings: What Does Success Look Like? Catalyzing Meeting Intentionality with AI-Assisted Prospective Reflection Before and during meetings: The CoExplorer Technology Probe: A Generative AI-Powered Adaptive Interface to Support Intentionality in Planning and Running Video Meetings During meetings: Are We On Track? AI-Assisted Active and Passive Goal Reflection During Meetings - Microsoft Research Between meetings: Designing Interfaces that Support Temporal Work Across Meetings with Generative AI